The perception of place branding as a mechanism in City planning in Alor Setar, Kedah - Fariha, Ramli (2019)
Competitions between places makes places strive to be better than their competitors. It has been the answer to the emergence of competition between the cities in showcasing places to attract intellectual elites, residents, tourists, investors, and anyone with an interest in the place. This study has emphasized on the capability of the place branding as one of the methods of place-image recovery in the context of city planning. Therefore, this research seeks to develop a place branding strategy from the users’ perspective, guided by the following objectives: (1) to define the meaning of place branding by government agencies, (2) to define the meaning of place branding by the local people, (3) to examine the perception of place branding was conceived, built, and used by the government agencies, (4) To explore the benefits and difficulties of place branding, (5) to formulate suitable strategic technique of place branding. A mixed method approach was adopted in data collection combining interview and questionnaire data. The interview session was conducted with 15 respondents comprising five members of Alor Setar City Council, five from Kedah State Department of Town and Country Planning, and the rest were officers from Tourism Malaysia Kedah. For quantitative data, this study has analysed the questionnaire responses from 384 respondents comprising of both local communities and visitors in Alor Setar. Both methods of data collection were carried out in 2016 and 2017. The interview data was analysed using the NVivo 10 software, whereas the Statistical Package for Social Science software was used to process quantitative data. The findings show that there is a positive perception among government agencies and city users on the idea of place branding in city planning. More interestingly, the findings also demonstrate that Alor Setar has the potential to set its own brand as a friendly and smart place, accessible to everyone as well as, capable of attracting users from diverse backgrounds of society. Hence, this study recommends the sixth steps approaches as one of the place branding strategies in city planning and suggests further research on place branding issues in other locations in Malaysia.